Instagram @infobnn_kota_surakarta sebagai media informasi Pencegahan Pemberantasan Penyalahgunaan Peredaran Gelap Narkotika (P4GN) - Rini Wijayanti (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2022)
The problem of drugs and their abuse has become a national and international threat. BNN as the leading drug handling sector in Indonesia carries out various efforts to prevent drug abuse, one of which is through the delivery of information P4GN (Pencegahan Pemberantasan Penyalahgunaan Peredaran Gelap Narkotika) through social media Instagram. The @infobnn_kota_surakarta account is used as a medium of information by BNN Surakarta City to the public. This study uses the theory of Denis Mcquail which states that new media as a medium for searching and disseminating information that creates connectedness of access (connectivity) between the sender and recipient of the message, and is interactive. The purpose of this study is to describe the use of Instagram @infobnn_kota_surakarta and can be used as a reference in disseminating information by government agencies in using Instagram. The method used in this research is descriptive qualitative. The primary data collection technique used interviews and documentation to 5 (five) related informants. Meanwhile, secondary data collection techniques used literature studies from books and online sources. The technique of validating the research data uses source triangulation. Based on the research that has been done on the account, the @infobnn_kota_surakarta account has been used as a medium for disseminating information that can connect account owners and their followers so that connectivity occurs and is interactive. Keywords: Instagram, P4GN, Information Dissemination